2011
DOI: 10.4038/jnsfsr.v39i2.3178
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxicity of a glyphosate herbicide, Roundup®, to two freshwater crustaceans

Abstract: The acute toxicity of a glyphosate herbicide Roundup ® , contaminating freshwater ecosystems in Sri Lanka was investigated with two species of the most common freshwater crustaceans: calanoid copepod (Phyllodiaptomus annae Apstein) and decapod shrimp (Caridina nilotica P. Roux). LC50 values in adult males were determined using standard toxicity assays under static conditions. The 48h LC50 value for P. annae was estimated as 1.06 mg/L and the values of 72 h and 96 h LC50 for C. nilotica were 107.53 and 60.97 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Inhibition of EPSPS enzyme production can be fatal to plants and animals. Ashoka Deepananda et al (2011) showed that 24 h exposure of glyphosate can kill 50% of Phyllodiaptomus annae as low as 1.059 mg/L. The present results showed that adult stage of P. annandalei (24 h LC 50 ; 11.70 mg/L Gly) demonstrated slightly better tolerant to glyphosate compared to the adult stage of Phyllodiaptomus annae as reported previously.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Inhibition of EPSPS enzyme production can be fatal to plants and animals. Ashoka Deepananda et al (2011) showed that 24 h exposure of glyphosate can kill 50% of Phyllodiaptomus annae as low as 1.059 mg/L. The present results showed that adult stage of P. annandalei (24 h LC 50 ; 11.70 mg/L Gly) demonstrated slightly better tolerant to glyphosate compared to the adult stage of Phyllodiaptomus annae as reported previously.…”
Section: Discussionsupporting
confidence: 86%
“…This could be attributed to variation in many biotic and abiotic factors such as geographical distribution, species, innate immune response etc. For instance, P. annae was collected from the rivers of Sri Lanka (Ashoka Deepananda et al, 2011), while P. annandalei in this study was collected from an estuary in Matang river, Kuala Sepetang, Perak, Malaysia. The climate and variation in abiotic environmental factors such as temperature, salinity, and diet preference could be direct or indirectly influent the biological reaction, metabolism and physiological changes of the copepods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have shown that the formulations and surfactant additives are usually more toxic to test species (Barceló and Hennion, 1995;Giesy et al, 2000). Studies on various organisms such as nematode, juvenile frogs, freshwater crustaceans, microalgae and sturgeons showed that they exhibit significant toxicity to these organisms (Achiorno et al, 2008;Bernal et al, 2009;Ermis and Demir, 2009;Deepananda et al, 2011;Filizadeh and Islami, 2011;Bates and Edwards, 2013;Piola et al, 2013). Removal of glyphosate from soils is best carried out by bioremediation often employing glyphosate-degrading bacteria as the low con-centration of glyphosate in polluted soils make other form of remediation such as chemical and physical more expensive and unpractical.…”
Section: Introductionmentioning
confidence: 99%